EFEKTIVITAS E-HEALTH DI RUMAH SAKIT UMUM DAERAH DR. M. SOEWANDHIE SURABAYA - avinda, avinda; Handoko, Rudy (JPAP: Jurnal Penelitian Administrasi Publik, 2017)
E-Health Effectiveness in General Hospital Region Dr. M. Soewandhie Surabaya. Public Service is the main obligation of the government to organize activities in order to meet the needs of the community. City officials do a service innovations as efforts to improve public services in the health sector by applying the principles of e-Government and one of these innovations is a service of E-Health. E-Health is an application that allows people to shorten queues at the clinic or hospital. The purpose of this study to determine the effectiveness of E-Health at the Regional General Hospital Dr. M. Soewandhie Surabaya. The focus of the study was based on Gibson's five effectiveness measurement indicators, namely Production, Efficiency, Satisfaction, Adaptability and Survival. The research method used is descriptive qualitative. The results of this study indicate that the service E-Health at the Regional General Hospital Dr. M. Soewandhie Surabaya is quite. It can be seen from Satisfaction Indicator, Adaptability and Survival. In satisfaction indicators, showed as many as 6 out of 10 patients stated that E-Healthservices already meet expectations. In adaptation indicators, show that E-Health services make it easier for the performance of the employees, especially employees of the registration window. On the Survival indicator, it shows that Dr. M. Soewandhie Surabaya as E-Health service providers already have plans to develop e-Health services in order to meet the needs of the community.Â Keywords: Public Service, Effectiveness, E-Health